Estimation of Statewide Origin–Destination Truck Flows from Large Streams of GPS Data: Application for Florida Statewide Model. Issue 1 (January 2015) - Zanjani, Akbar Bakhshi; Pinjari, Abdul R.; Kamali, Mohammadreza; Thakur, Aayush; Short, Jeffrey; Mysore, Vidya; Tabatabaee, S. Frank
This paper demonstrates the use of large streams of truck GPS data from the American Transportation Research Institute for the estimation of statewide freight truck flows in Florida. Raw GPS data streams, which comprised more than 145 million GPS records, were used to derive a database of more than 1.2 million truck trips that started or ended in Florida. The paper sheds light on the extent to which the trips derived from the GPS data captured the observed truck traffic flows in Florida. The paper includes insights into ( a ) the truck type composition, ( b ) the proportion of the observed truck traffic flows covered by the data, and ( c ) the geographical differences in the coverage. The paper applies origin–destination (O-D) matrix estimation to combine the GPS data with the observed truck traffic volumes at different locations within and outside Florida to derive an O-D table of truck flows within, into, and out of the state. The procedures, implementation details, and findings discussed in the paper are expected to be useful to agencies that are considering the use of GPS data in freight travel demand modeling.